Dietary isoleucine requirement of juvenile blunt snout bream, Megalobrama amblycephala. (30th November 2015) - Ren, M.; Habte‐Tsion, H.‐M.; Liu, B.; Miao, L.; Ge, X.; Xie, J.; Zhou, Q.
Abstract: A 9‐week feeding trial was conducted to estimate the dietary isoleucine requirement of juvenile blunt snout bream. Six isonitrogenous and isoenergetic experimental diets were formulated to contain graded isoleucine levels ranging from 5.3 to 20.1 g kg −1 dry diet. At the end of the experiment, weight gain (WG), specific growth rate (SGR), feed efficiency ratio (FER) and protein efficiency ratio (PER) increased with increasing dietary isoleucine level up to 11.1 g kg −1 dry diet, and dietary isoleucine level above 14.2 g kg −1 dry diet declined these performances. Dietary isoleucine levels (14.2 and 17.3 g kg −1 dry diet) significantly improved whole‐body protein content, but decreased whole‐body lipid, plasma triglyceride and cholesterol contents. Significantly lower visceral fat index (VFI) in fish fed with 14.2 g kg −1 dietary isoleucine was observed compared to those fed with deficient or excessive isoleucine. Dietary isoleucine supplementation significantly increased plasma isoleucine concentration, while plasma valine and leucine concentrations showed a reversed trend. Dietary isoleucine levels regulated the target of rapamycin (TOR) gene expression and improved plasma superoxide dismutase (SOD) activity in juvenile blunt snout bream. Based on second‐order polynomial regression model analysis of SGR and FER, the optimum dietary isoleucine requirement was estimated to be 13.8 g kg −1 dry diet (40.6 g kg −1 dietary protein) and 14.0 g kg −1 dry diet (41.2 g kg −1 dietary protein), respectively.